Restricción en el horario de venta de licor como política de protección interna y orden público, en la parroquia de Vilcabamba y su incidencia en el sector turístico en el periodo 2015” - Carrera Enríquez, Jessica del Cisne (2017)
The main purpose of the present investigation is to determine the impact of the restriction on the time of sale of liquor in the Vilcabamba parish tourism sector, as a security policy in the period 2015, the approach and development part of identifying the results that Has had the application of the public policy, also determine if the strategies proposed in the policy of internal security and public order are being fulfilled in the best way according to the objectives of the policy. This work is important because of the possibility of identifying the control mechanisms applied by the authorities to comply with the provisions of the different decrees, ordinances, ministerial agreements and other established norms that are related to the issue, issued to Consumers as places of sale of alcoholic beverages, as well as publicizing the problems that this type of beverages and narcotic and psychotropic substances generate in health, society and the different sectors that contribute to the advancement of the parish. The results obtained during the research process allow us to determine that the implementation of the restriction policy in the liquor sales schedules has had no impact on the tourism sector of the parish of Vilcabamba.